Alterations of putaminal shape in de novo Parkinson's disease. Issue 5 (16th February 2016) - Caligiuri, Maria Eugenia; Nisticò, Rita; Arabia, Gennarina; Morelli, Maurizio; Novellino, Fabiana; Salsone, Maria; Barbagallo, Gaetano; Lupo, Angela; Cascini, Giuseppe Lucio; Galea, Domenico; Cherubini, Andrea; Quattrone, Aldo
ABSTRACT: Introduction: Several neuroimaging studies have been carried out to gain insight on the pathological processes that cause PD, but literature findings are inconsistent. The aim of this study was to combine information carried by functional imaging with DA transporter ligands and structural MRI. Methods: Forty‐two untreated, de novo‐PD patients and 30 control subjects were involved in this study. Patients were divided in subgroups according to the presence of uni‐ or bilateral reduction of ligand uptake in the putamen, as observed on DA transporter single‐photon emission tomography: 12 patients had abnormal uptake in the right putamen and 11 in the left, whereas 19 had bilateral abnormal uptake. Voxel‐based morphometry and shape analysis were used to compare healthy subjects to all de novo‐PD or to patients with either right or left abnormal uptake. Results: Shape analysis identified significant differences between de novo‐PD and controls in putaminal regions. In patients with unilateral abnormal uptake, only the medial surface of the structure was involved. When patients with bilateral uptake reduction were also considered, changes extended from the medial to the lateral surface of putamina. Voxel‐based morphometry showed similar results to those detected with shape analysis, but it failed to identify the putaminal subfield involved in patients with asymmetric or symmetric damage on DA transporter single‐photon emission tomography. Conclusions: Shape analysis in de novo‐PD patients suggested a progressive medial‐to‐lateral involvement of the putamina that paralleled an asymmetric‐to‐bilateral distribution of DA transporter depletion. © 2016 International Parkinson and Movement Disorder Society